Fragment analysis represents a suitable approach for the detection of hotspot c.7541_7542delCT NOTCH1 mutation in chronic lymphocytic leukemia - Vonková, Barbara (Jihočeská univerzita, 2018)
Chronic lymphocytic leukemia is the most common type of leukemia in adults in western countries. Despite the continual improvement of diagnostic methods and treatment, it still remains incurable. One of the main characteristic features of CLL is its clinical and biological variability. In present, the analysis of prognostic genetic markers is the most useful tool for understanding biology and clinical course of the disease and consequently the individual type of treatment. The presence of a NOTCH1 mutation is connected with shortened survival and resistance to conventional chemo-immunotherapy. In this thesis, we examined CLL patients with c.7541_7542delCT NOTCH1 mutation and the most sensitive and specific method was identified. We compared nowadays most commonly used methods: allele-specific PCR, fragment analysis and Sanger sequencing.
Fragment analysis represents a suitable approach for the detection of hotspot c.7541_7542delCT NOTCH1 mutation in chronic lymphocytic leukemia
Keywords: CLL; NOTCH1 mutation; fragment analysis; sequencing; allele-specific PCR; CLL; NOTCH1 mutation; fragment analysis; sequencing; allele-specific PCR